2001
DOI: 10.1093/bja/86.1.44
|View full text |Cite
|
Sign up to set email alerts
|

Recovery and neurological examination after remifentanil–desflurane or fentanyl–desflurane anaesthesia for carotid artery surgery

Abstract: We studied 44 patients undergoing carotid endarterectomy (CEA) to compare recovery after general anaesthesia with desflurane supplemented with either remifentanil or fentanyl. Remifentanil was infused at 0.1 microg kg(-1) min(-1) and desflurane was adjusted at 2 vol% end-tidal. Fentanyl was given as a bolus dose of 2 microg kg(-1) before induction and repeated at skin incision; desflurane was adjusted as needed. Times for early recovery and response to simple neurological tests (digit symbol substitution test … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0
6

Year Published

2003
2003
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(26 citation statements)
references
References 13 publications
1
19
0
6
Order By: Relevance
“…Studies were excluded when dealing with pharmacology recovery after anesthesia (nϭ2), 11,12 lacking postoperative assessment (nϭ1), 13 case reports (nϭ2), 14,15 review articles (nϭ4), [7][8][9][10] or ongoing trials without available results (nϭ3). One study was considered a duplicate 16 of another included study 17 (Figure).…”
Section: Search Resultsmentioning
confidence: 99%
“…Studies were excluded when dealing with pharmacology recovery after anesthesia (nϭ2), 11,12 lacking postoperative assessment (nϭ1), 13 case reports (nϭ2), 14,15 review articles (nϭ4), [7][8][9][10] or ongoing trials without available results (nϭ3). One study was considered a duplicate 16 of another included study 17 (Figure).…”
Section: Search Resultsmentioning
confidence: 99%
“…In order to prevent a high dynamic response and choking in the recovery process of general anesthesia and extubation, many methods, such as deep anesthesia extubation, the use of local anesthetics, vasodilators, short-acting opioid drugs, and other methods, have been used in the clinic (Shajar et al, 1999;Hohlrieder et al, 2007). Studies have reported that the application of general anesthesia with propofol or remifentanil could make the recovery process of patients smoother (Shajar et al, 1999;Wilhelm et al, 2001;Blayney et al, 2003;Hohlrieder et al, 2007). However, propofol and remifentanil, which are more conducive to allowing patients to pass through the recovery period safely, have been less characterized.…”
Section: Discussionmentioning
confidence: 99%
“…It has been widely used in clinical anesthesia (Hughes et al, 1992;Kapila et al, 1995;Soltesz et al, 2001). Recent studies have shown that the use of remifentanil can benefit patients who are awake (Shajar et al, 1999;Wilhelm et al, 2001;Hohlrieder et al, 2007). The purpose of this study was to investigate the effect of maintaining an intravenous infusion of remifentanil or propofol on the performance of general anesthesia, including the cardiovascular response, choking, and irritability at the end of general anesthesia, in order to assess the effect of a maintenance intravenous infusion of remifentanil or propofol.…”
Section: Introductionmentioning
confidence: 99%
“…with a regional technique). Clinically, remifentanil titratability translates into a better control over adrenergic stimuli whatever the type of surgery or the patients (Kapila et al 1995;Mouren et al 2001;Schuttler et al 1997;Cartwright et al 1997;Gemma et al 2002;Guy et al 1997;Howie et al 2001;McGregor et al 1998;Sneyd et al 2001;Ahonen et al 2000;Balakrishnan et al 2000;Casati et al 2000;Doyle et al 2001;Fleisher et al 2001;Natalini et al 1999;Twersky et al 2001;Wee et al 1999;Wilhelm et al 2001). For example, intubation is a stronger stimulus than laryngoscopy, which in turn is stronger than skin incision.…”
Section: Control Over Intra-operative Stimulimentioning
confidence: 99%